Jean-Gaspard Deburau: Romantic Pierrot - Nye, E (Cambridge University Press, 2014)
Jean-Gaspard Deburau was the nineteenth-century mime artist who created a new model for subsequent performers to either imitate or reject, but hardly to ignore. Silent cinema benefited from the nineteenth-century vogue for the mime in general – and the Pierrot character that he did so much to popularize in particular. The most famous mime of the twentieth century, Marcel Marceau, derived his character ‘Bip’ in part from Deburau's Pierrot. And while two of the most influential French mime artists of the twentieth century, Jean-Louis Barrault and Étienne Decroux, sought a radical departure from his Pierrot tradition, they ironically found themselves in the now legendary French film Les Enfants du paradis acting the parts respectively of Deburau and Deburau's father. In this article Edward Nye explores the reasons for Deburau's success from two perspectives: first, by considering Deburau's reputation for clarity of expression, and the absence of critical or public debate over any obscurity; and second, the context of the Romantic movement which primed spectators to appreciate his style of performance. Edward Nye is Fellow of Lincoln College, Oxford, and University Lecturer in French. He has published on seventeenth- and eighteenth-century subjects in French literature and the arts, notably Mime, Music, and Drama on the Eighteenth-Century Stage: the Ballet d'Action (CUP 2011), Literary and Linguistic Theories in Eighteenth-Century France (OUP, 2000), and on the literary aesthetics of sports writing, in À Bicyclette (Les Belles Lettres, 2000).